2021
DOI: 10.3390/coatings11091136
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of a Plasma-Oxidized Ti6Al4V Alloy for Dental Applications

Abstract: A Ti6Al4V alloy was plasma-oxidized at 600 °C during 1, 2, 3, 5 and 8 h and corroded in an artificial saliva solution. Electrochemical evaluation was performed by using potentiodynamic polarization curves, linear polarization resistance (LPR), and electrochemical impedance spectroscopy (EIS) measurements during 100 h. Corroded specimens were characterized by using Raman spectroscopy and scanning electronic microscopy (SEM). All tests indicated that the highest corrosion resistance was obtained for specimen oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…The increase in the polarization resistance values in the case of the nanoporous TiO 2 film electrochemically formed on titanium alloy was due to the presence of the TiO 2 layer that provided superior insulating properties through its electrochemically controlled formation. This behavior has also been observed in the specialized literature by other authors with other biomaterials [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. For the electrochemically oxidized grade 5 Ti6Al4V alloy, an increase in the polarization resistance values was observed with increasing immersion time; for the untreated grade 5 Ti6Al4V alloy, it was observed that the polarization resistance values showed a slight decrease after 38 h of immersion in comparison to the value obtained after 360 min, and a slight increase at the end of the immersion period.…”
Section: Evolution Of the Polarization Resistance (Rp) Vs Time In Han...supporting
confidence: 78%
See 2 more Smart Citations
“…The increase in the polarization resistance values in the case of the nanoporous TiO 2 film electrochemically formed on titanium alloy was due to the presence of the TiO 2 layer that provided superior insulating properties through its electrochemically controlled formation. This behavior has also been observed in the specialized literature by other authors with other biomaterials [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. For the electrochemically oxidized grade 5 Ti6Al4V alloy, an increase in the polarization resistance values was observed with increasing immersion time; for the untreated grade 5 Ti6Al4V alloy, it was observed that the polarization resistance values showed a slight decrease after 38 h of immersion in comparison to the value obtained after 360 min, and a slight increase at the end of the immersion period.…”
Section: Evolution Of the Polarization Resistance (Rp) Vs Time In Han...supporting
confidence: 78%
“…This behavior can be explained by the formation of a more stable and protective thin oxide film on the surface of the electrochemically oxidized alloy, which acts as a protective film to prevent the release of metal ions into the biological environment. The trend toward higher values in the case of different types of materials obtained by electrochemical oxidation compared to different untreated alloys has also been observed by other authors in the specialized literature [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The comparative evolution of the polarization resistance for the untreated grade 5 titanium alloy and for the electrochemically oxidized titanium alloy with the nanoporous film of titanium oxide (TiO 2 ) is presented in Figure 8a-c at three time periods in the total sample immersion period in Hank's biological solution.…”
Section: Titanium Oxide Film Electrochemically Formed On the Surface ...supporting
confidence: 77%
See 1 more Smart Citation
“…The results showed that adding ZnMOF-BTA to 1M hydrochloric acid solution inhibits corrosion processes and protects carbon steel from degradation. The results also revealed that the inhibition efficiency of ZnMOF-BTA is greater than the inhibition efficiencies of some MOFs reported in the literature [46].…”
Section: Weight Loss Measurementmentioning
confidence: 48%
“…EIS is a method with a wide range of uses, including the detection of biomarkers and cellular deformities in physiological fluids, detection of food-borne pathogens and cancer cells, as well as the investigation of metal corrosion and coated metal surfaces [ 17 ]. In the dentistry field, EIS spectroscopy is primarily used for the examination of dental materials, corrosion and mycosis identification [ 18 21 ]. EIS analysis of saliva is limitedly studied despite promising potential as a diagnostic tool for oral and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%